Pencurian Buah Kelapa Sawit di Desa Muda Setia Kecamatan Bandar Sei Kijang Kabupaten Pelalawan - Wildoh, Wildoh; Yusuf, Yusmar (Peneliti.net, 2025)
This research was conducted in Muda Setia Village, Bandar Sei Kijang District, Pelalawan Regency with the aim of knowing the phenomenon and efforts to overcome the theft of oil palm fruit that occurs. This research used a descriptive qualitative method by taking 8 (eight) informants. This research uses purposive sampling techniques and data is collected through observation, interviews and documentation. The theory used in this research is social control theory. The results of this research in the field can be concluded that many people feel restless and disturbed due to the theft of oil palm fruit. Oil palm fruit theft is very common and the perpetrators of the theft are not other people but people from Muda Setia Village as well. So community efforts are needed to overcome cases of oil palm fruit theft. The efforts, namely preventive efforts, are efforts to handle or prevent theft of oil palm fruit, and repressive efforts are efforts that are more focused on action or control after theft of oil palm fruit occurs.